Traumatic Brain Injury - Kumar, Rajiv (Innovative Journal of Medical and Health Sciences, 2021)
More than seven million Americans have suffered a stroke, and at an economic burden of billions annually. Among these cases, ischemic stroke is the only leading cause that accounts for more than 80% of cases of stroke patients. Almost 100% of patients who are being affected by severe and moderate head injury will not regain the pre-morbid level of ability and will be permanently disabled. Therefore, TBI is one of the leading causes of morbidity and mortality globally, particularly among young people. Following the World Health Organization (WHO), nearly five million people lost their lives per year from traumatic injuries worldwide. Moreover, brain ischemia is also underlined as a key cause of death and adult brain disability. Enormous progress has been made in drug discovery, even though a lot of uncertainty persisted in the methodology adopted in treating traumatic brain injury (TBI) and diseases. In severe conditions, these injuries are untreatable and considered fatal diseases.